2000
DOI: 10.1017/s0950268899004513
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a serological Salmonella Mix-ELISA for poultry used in a national surveillance programme

Abstract: A Mix-ELISA using lipopolysaccharide antigens from Salmonella enterica serotype Enteritidis and Typhimurium was evaluated using samples collected over time in the Danish salmonella surveillance programme for poultry. Serological samples (n = 42,813) taken from broiler-breeder flocks after a year of bacteriological monitoring with negative results were used for calculating the flock and individual test specificities, which were 0.997 and 0.999, respectively. Layer flocks from the table egg sector were used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…The work described in the current study has shown that infection within a breeding company can be effectively controlled by application of good hygienic procedures following culling of infected flocks. It is more difficult to prevent introduction of infection, especially as vaccination of layer parent flocks is not used since infection is rare, biosecurity is good and vaccination would remove the ability to use sensitive serological monitoring for breeding flocks (Nicholas & Andrews, 1991;Feld et al, 2000). This study has demonstrated important points about control of infection in large-scale poultry operations.…”
Section: Discussionmentioning
confidence: 93%
“…The work described in the current study has shown that infection within a breeding company can be effectively controlled by application of good hygienic procedures following culling of infected flocks. It is more difficult to prevent introduction of infection, especially as vaccination of layer parent flocks is not used since infection is rare, biosecurity is good and vaccination would remove the ability to use sensitive serological monitoring for breeding flocks (Nicholas & Andrews, 1991;Feld et al, 2000). This study has demonstrated important points about control of infection in large-scale poultry operations.…”
Section: Discussionmentioning
confidence: 93%
“…The large amount of work carried out in development and operation of the Danish Salmonella control policy has shown that a pragmatic approach to categorize herds on the basis of Salmonella antibody seroprevalence can be an effective tool for identifying highly infected herds (Mousing et al 1997;van der Wolf et al 2001a), and this approach has been adopted in several other countries worldwide (Ludewig and Fehlhaber 2001) and in other target species (Hoorfar et al 1997;Feld et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Immunological detection by serology can also be used to identify indirect evidence of likely exposure to Salmonella by detecting antibodies in serum or egg yolk (Davies et al, 1997;Feld et al, 2000). This increases the sensitivity of detection of those serotypes whose surface antigens are included in the ELISA-based test, normally S. Enteritidis and S. Typhimurium, compared with bacteriology alone, and a combination testing programme has been successfully used in Denmark for many years (Wegener et al, 2003).…”
Section: Sampling Methodsmentioning
confidence: 99%